Antiphotocorrosion UV‐Bi2O3@PANI Photocatalyst Rich in Oxygen Vacancy Defects: Building Processes, Preparation Mechanisms, and Photocatalysis Performance. Issue 23 (7th October 2022) - Dou, Wenyue; Kong, Linghao; Hu, Xingyun; Tan, Zhenzhen; Yang, Yangyang
Abstract : Low content of oxygen vacancy defects (OVs) and limited resistibility to photocorrosion are the core problems in the heterogeneous photocatalytic processes of bismuth oxide (Bi2 O3 ). Herein, the strategy of "ultraviolet (UV) light‐inducing OVs" coupling with "polyaniline (PANI) combination inhibiting photocorrosion" is employed on the modification of Bi2 O3 . First, the high methylene blue (MB) degradation efficiency by UV3h ‐Bi2 O3 @PANI0.5 wt% above 99.5% and the low Bi 3+ dissolved concentration below 0.20 mg L −1 under visible light signify the high photocatalytic activity and stability. Then, the mechanisms for generation of OVs and inhibition of photocorrosion are proposed as follows. 1) Holes (h + ) forming under irradiation, diffusing through the lattice, and reaching the surface of Bi2 O3 can be regarded as a monatomic oxygen ion (OS − ); 2) OS − combines and continues to be oxidized by h +, leading to the generation of O2 with the OVs left in the lattice; 3) UV‐Bi2 O3 and PANI are excited to produce electrons/holes (e − /h + ); 4) e − /h + transfer in UV‐Bi2 O3 @PANI heterojunction leads to the separation of h + from UV‐Bi2 O3 and the inhibition of photocorrosion. Through the core problems being overcome, a new idea for the development and application of Bi2 O3 with excellent performances in the field of water treatment is provided. Abstract : A new bismuth oxide (Bi2 O3 ) photocatalyst with high photocatalytic activity and stability is synthesized based on the strategy of "ultraviolet (UV) light inducing oxygen vacancies (OVs)" coupling with "polyaniline (PANI) combination inhibiting photocorrosion". OVs form under UV light, thanks to the oxidation of oxygen ion (O 2− ) in Bi2 O3 by holes (h + ). Transfer of electrons/holes (e − /h + ) in UV‐Bi2 O3 @PANI heterojunction inhibits the photocorrosion.